Peran Strategis Bahasa Indonesia dalam Pembentukan Nilai Karakter Anak - Masayu Gay (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This papers aims to describe the role of language in shaping the character values of children. Libraries research is used to review Munir’s concept of the character which emphasis on the thoughts, attitudes, words and deeds, as well as Widjono’s concept of character which studies the relationship between language and character. This paper concludes that Indonesian language is not just a means of communication, but it can also become a means which influence the way of thinking of its speakers, which in turns reflects the character of its speakers. The character values are reflected on the utterances in daily speaking. This means that language takes an important role in building the character of its speakers through communication. The pattern of positive communication impacts on the formation of a positive character values. Children are unstable individuals. They are prone to grow and develop unstable due to their surroundings. The patterns of communications received through authority parties such as the parents, teachers, or friends will be received as the correct information which will shape their characters.